TEMPAT-TEMPAT SAKRAL DAN PENERAPAN SAWORA DALAM MASYARAKAT KAMPUNG ISENEBUAI DI KAWASAN TAMAN TELUK CENDERAWASIH - Irman Rumengan (Sabda: Jurnal Kajian Kebudayaan, 2017)
Cultural heritage is an important value owned by some communities in the area of Teluk Cenderawasi National Park. One of which is the legacy of important places owned by Isenebuai village community. Isenebuai village community has Sawora or "oath" to organize and manage the resources, location owned. The implementation of Sawora by Isenebuai village community has been done for a long time. The implementation of Sawora has also been applied to the villagers and the community outside of Isenebuai village, with the rules made by the adat elders and community leaders of Isenebuai village. Sawora and important places of Isenebuai village are a very unique cultural treasure owned by the village community specifically and owned by the Cendrawasih Bay National Park Area in general. In general, Sawora has similarities with Sasi but has a very different implementation base, because Sawora is the original product of Isenebuai village community culture that has existed since long time (before the introduction of Sasi).